Back to Surau: Redefining Early Childhood Character Education Through the Lens of Minangkabau Culture - Syafrida, Rina; Riana, Nancy; Karnia, Nia; Ismail, Marzeni (Al-Athfal: Jurnal Pendidikan Anak, 2025)
Purpose – This study aims to explain the rationale behind the "Back to Surau" research, particularly the importance of the surau-based approach in early childhood character education. The study is motivated by concerns over the degradation of children's moral values and the belief that re-establishing the surau as a center for character education can strengthen moral and noble values in early childhood.Design/methods/approach – This study employed a qualitative phenomenological approach to explore the experiences of Quran teachers, parents, and community leaders in integrating surau values into early childhood character education. A total of 23 purposively selected participants were involved, including 5 Quran teachers, 6 parents, 2 traditional or religious leaders, and 10 early childhood children (through observation). Data were collected via semi-structured interviews, participatory observation at four selected suraus (two in regency areas and two in urban settings), and document analysis. Thematic analysis followed Miles and Huberman’s (1994) framework—data reduction, presentation, and conclusion drawing—while van Manen’s phenomenological principles guided the interpretation. Research ethics were maintained through informed consent, confidentiality, and cultural sensitivity.Findings – Six major themes emerged. First, the surau functions as a center of moral and spiritual learning for young children. Second, community involvement and local culture in the surau enrich character education. Third, integrating religious values and local wisdom into daily activities is effective in shaping positive character. Fourth, meaningful learning experiences in the surau foster empathy, discipline, and responsibility. Fifth, support from families and surau management is a key success factor for this approach. Sixth, challenges such as time constraints and modern lifestyles must be addressed when adapting surau values to the formal education context.Research implications/limitations – This study is limited to a specific cultural community (Minangkabau), limiting the generalizability of the results. However, the findings provide insights into the potential of local wisdom as a character education strategy.Practical implications – This study encourages early childhood educators and policymakers to integrate surau-based approaches into curricula and school activities. This approach can serve as a model for character building through collaboration among schools, families, and communities.Originality/value – This research is original in reviving the role of the surau and Minangkabau local wisdom in early childhood education. Its novelty lies in integrating a local traditional institution with modern educational practices to strengthen the character of the young generation.Paper type Research paper